Integrating Treatment for Autism: Psychiatric Comorbidities and Comprehensive Treatment - C.I. Parenteau; R.M. Tsipan; R.L. Hendren (Moscow State University of Psychology and Education, 2021)
Autism Spectrum Disorder (ASD) treatment becomes more convoluted when additional mental disorders are present. Comorbidities with ASD discussed in this review include attention deficit hyperactivity disorder (ADHD), anxiety, depression, disruptive mood dysregulation disorder (DMDD), psychotic and bipolar disorder. As these disorders typically affect multiple endophenotypes, from genetics to behavior, treatment must aim to target multiple layers, all the while minimizing side effects. Evidence-based therapies for ASD and comorbidities can range from psychosocial interventions to psychotropic medicines, with a varying degree of effectiveness for pairings of comorbidities and combinations of treatment. This review aims to create a brief overview of ASD comorbidities and discuss treatment options based on prior evidence-based research. Appropriate treatment is dependent on specific symptomatology, but evidence suggests that integrative-targeted treatment is typically more effective than stand-alone treatments.